Changing trends in HIV diagnosis in an inner city London teaching hospital 2007–2011. (April 2013) - Wilkin-Crowe, H; Majewska, W; Lau, R; Webb, H; Pakianathan, M
Summary: In 2008, guidelines aimed at reducing undiagnosed HIV infection were published, recommending normalization of testing. Local initiatives were carried out in south-west London including an extensive primary care education programme. This study aimed to establish the impact of these initiatives on HIV diagnoses. Data on all new diagnoses referred to our centre were collected and analysed from patient records. A total of 394 patients were newly diagnosed with HIV from 2007 to 2011. Diagnosis in primary care and other non-sexual health (SH) settings increased by 184% during this period. There was an increase of 37% in the median CD4 count at diagnosis, taking the figure to 372 cells/mm 3 in 2011. The proportion of patients presenting with a CD4 count of <200cells/mm 3 decreased by 24%. The evidence suggests that these local initiatives were successful in increasing HIV diagnoses outside SH settings, particularly in very late presenters.